Are platelet indices useful in the evaluation of type 2 diabetic patients? - Kamilla R. Alhadas; Sandra N. Santos; Marcela Mara S. Freitas; Sophia Mara S. A. Viana; Luiz Claudio Ribeiro; Monica B. Costa
ABSTRACT Introduction: Long-term complications of diabetes mellitus are a leading cause of death in people with diabetes. Recent studies suggest that platelets with altered morphology could be associated with an increased risk for developing vascular complications in diabetes. Objective: To evaluate the platelet parameters in diabetic patients and correlate these indices with microvascular and macrovascular complications of the disease. Materials and methods: We analyzed platelet parameters and biochemical data of patients seen in outpatient clinics of a university hospital. Individuals aged between 30 and 60 years were included, 100 patients with type 2 diabetes mellitus (T2DM) (DM group) and 100 non-diabetic patients (control group). Results: We observed increase in plateletcrit (PCT): 0.21 ± 0.054% vs 0.20 ± 0.045% (p = 0.020); in mean platelet volume (MPV): 8.69 ± 1.288 fl vs 8.27 ± 1.244 fl (p = 0.018); and in platelet distribution width (PDW): 17.8 ± 1.06 fl vs 17.5 ± 0.87 fl (p = 0.039) in the DM and control groups, respectively. Values of MPV, PCT, and PDW were higher among patients with complications of T2DM (p < 0.001). In those with macrovascular disease, we observed a correlation between glycated hemoglobin (A1C) and MPV (p = 0.015) and PDW (p = 0.009) levels. Among patients with microvascular complications, there was a correlation between platelet count and MPV with A1C levels (p < 0.001). Conclusion: The study findings point to significant differences in platelet parameters in patients with T2DM, suggesting the presence of more reactive and aggregatable platelets in this group of individuals. These results suggest that platelet evaluation may be useful in the early detection of long-term complications in diabetic patients, considering that it is a simple and low-cost tool.